The Challenging Management of Short Bowel Syndrome - Ismini Kountouri; Afroditi Faseki; Alexandra Panagiotou; Christina Sevva; Ioannis Katsarelas; Dimitrios Chatzinas; Konstantinos Papadopoulos; Vasilis Stergios; Stylianos Mantalovas; Vasileios Alexandros Karakousis; Panagiotis Nachopoulos; Athanasios Polychronidis; et al. (Diagnostics, 2025)
A 62-year-old female presented to the Emergency Department of the General Hospital of Katerini, Greece, complaining of abdominal pain, fever, and general discomfort. Laboratory tests indicated an elevated white blood cell count and an elevated C-reactive protein level. A computed tomography (CT) scan revealed dilated small bowel loops and free intraperitoneal fluid. During laparotomy, extensive ischemia and necrosis of both the small and large bowel were discovered, and a resection of the small bowel and the right colon was performed, leaving the patient with only 90 cm of small intestine and a jejunocolic anastomosis. Postoperative management was particularly challenging, requiring a multidisciplinary approach, an intensive care unit stay, reoperations due to anastomotic leaks, continuous parenteral nutrition and electrolyte management, and aggressive antibiotic treatment for persistent bacterial infections. This case report highlights the importance of appropriate management of this life-threatening complication following extensive bowel resection.